Shrinkflation in the food industry: a review of market strategies, labeling, and consumer perception (Research, Society and Development, 2026)
In an unstable global economic scenario, marked by volatility in raw material costs and tax complexity, shrinkflation has established itself as a strategy within the food industry to mitigate inflationary pressures. The practice consists of reducing the net content of products without a proportional decrease in the final price. This study aims to conduct a bibliographic review of the phenomenon, examining its economic implications, its framework within labeling regulations, and its repercussions on consumer rights and public perception. The methodology is based on a narrative review, compiling data from databases such as SciELO and Google Scholar, as well as regulations from institutions like IBGE, ABIA, and ANVISA. The findings indicate that shrinkflation is interpreted by the sector as an "incremental innovation" necessary for financial sustainability. Although Brazilian legislation permits quantitative changes, it imposes the duty to clearly inform the modification on the main label panel for a determined period. However, consumer perception is mostly negative, characterized by feelings of betrayal and loss of brand trust, influenced by psychological and behavioral factors. From the perspective of the Consumer Defense Code (CDC), the practice borders on misleading advertising when the omission of information or lack of transparency misleads the individual regarding the product's real value. It is concluded that shrinkflation, while legitimate under a strict regulatory prism, demands greater ethics and responsibility, representing a critical opportunity for improving regulations and developing more honest and transparent market strategies.